Protection motivation theory and pro‐environmental behaviour: A systematic mapping review. (20th September 2019) - Kothe, Emily J.; Ling, Mathew; North, Madelon; Klas, Anna; Mullan, Barbara A.; Novoradovskaya, Lisa
Abstract: Objective: Climate change and related issues associated with the interaction of humans with the environment are of great importance in today's context. More and more research is focusing on understanding what can be done to prevent and reverse the effects of environmental problems through individual behaviours. Within psychology, there is a lack of synthesis of what drives pro‐environmental behaviours in various paradigms and how they can be changed. The current study focuses on the application of protection motivation theory to predicting and changing pro‐environmental behaviours using a systematic mapping approach. Methods: A systematic screening of 132 databases was performed, resulting in the identification of 22 relevant studies with the total N = 12, 827. Results: Investigation of the included research revealed a number of gaps in knowledge including: lack of experimental evidence with successful manipulations of protection motivation theory constructs; non‐inclusion of all the aspects of the theory into studies; the absence of examination of the intention–behaviour relationship; the lack of consistency in operationalisation of protection motivation theory constructs; a focus on predominantly western high income societies, and the lack of uniformity in the definition of pro‐environmental behaviours. Conclusion: Future research should consider employing experimental designs with proper manipulation checks and longitudinal focus, as well as consistent definitions and operationalisations of relevant concepts, and exploring these constructs across different countries.